2023
DOI: 10.2147/dmso.s400995
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Maternal Serum Cortisol and Maternal Insulin Resistance and Fetal Ultrasound Characteristics in Gestational Diabetes Mellitus

Abstract: Introduction Cortisol is proven to play a crucial role in hyperglycemia and fetal development in gestational diabetes mellitus (GDM). This research aims to investigate the relationship between maternal serum cortisol and insulin resistance indices and fetal ultrasound characteristics in women with GDM. Methods A cross-sectional and descriptive study on 144 GDM in Vietnam from January 2015 to December 2020. Serum cortisol was measured using electrochemiluminescence immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The insulin-like growth factor (IGF) pathway is a major fetal and placental growth-promoting pathway modified by DNA methylation of its components such as IGF2 and IGF binding proteins and is associated with fetal overgrowth in GDM [ 12 , 13 ]. In addition, the hypothalamic–pituitary–adrenal (HPA) axis mediates response to intrauterine stress, including hyperglycemic stress, and has demonstrated either a positive or a negative association with birth weight in different studies [ 14 , 15 ]. Chronic elevation of the effector hormone in this axis, cortisol, is associated with hypertension, type 2 diabetes mellitus, and mental health issues [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor (IGF) pathway is a major fetal and placental growth-promoting pathway modified by DNA methylation of its components such as IGF2 and IGF binding proteins and is associated with fetal overgrowth in GDM [ 12 , 13 ]. In addition, the hypothalamic–pituitary–adrenal (HPA) axis mediates response to intrauterine stress, including hyperglycemic stress, and has demonstrated either a positive or a negative association with birth weight in different studies [ 14 , 15 ]. Chronic elevation of the effector hormone in this axis, cortisol, is associated with hypertension, type 2 diabetes mellitus, and mental health issues [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hyperglycemic state is closely associated with insulin resistance ( Brown and Goldstein, 2008 ; Huri et al, 2014 ). Insulin resistance is positively correlated with elevated cortisol levels ( Lehrke et al, 2008 ; Nguyen et al, 2023 ), which have been shown to facilitate an increase in aggressive behaviors ( Alink et al, 2008 ; Azurmendi et al, 2016 ). This could be a significant contributing factor to the more frequent aggressive behavior observed in the boldness group of Tibetan macaques.…”
Section: Discussionmentioning
confidence: 99%
“…However, on day 7, the animals were immediately collected, weighed, and immediately returned to the dams. According to previous studies, day 7 represents a neonatal/newborn development period which loosely correlates with similar developmental stages in humans (summarised in Table 3 [196][197][198]. The animals were kept with their mothers for a period of 21 days/3 weeks under standard laboratory conditions (for temperature and humidity) in a 12 h day and 12 h night cycle.…”
Section: Male Pups Were Collected For the Studymentioning
confidence: 99%